Der Zolltarif als Trumpfkarte - Harold James (Wirtschaftsdienst, 2024)
The trade policies of the new Trump Administration will lead to job losses and higher consumer prices. Moreover, the emphasis on bilateral trade balances is likely to be restrictive. The current protectionist tide is due to the lack of an honest public debate about the potential benefits of free trade. Referendums could reveal voters' preferences between tariffs and alternative sources of income. Data-driven policymaking would be a counterweight to politically motivated protectionism and could pave the way for a new wave of globalisation.
Keywords: F13; F42; N72; P11; 330